Negosiasi Makna dan Transformasi Sakralitas Simbol: Dialektika Tawhid dan Tradisi pada Kepercayaan Kain Kuning Keramat di Banjarmasin - Padlianor Padlianor; Desyana Mustafa; Zulfa Jamalie (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
This study investigates the Islamization process of the meaning and symbolic sacredness in the Banjar community's reverence for the sacred yellow cloth. Amid a robust Islamic identity, this practice fosters a dialectic between local tradition and tawhid (monotheism). This research aims to analyze the Islamization of meaning, the internalization of Quranic values, and the reinterpretation of symbolic sacredness to align with monotheistic principles. Employing a descriptive qualitative approach, the methodology combines field studies at the Kubah Habib Hamid bin Abbas Bahasyim with tafsir maudhu‘i (thematic Quranic exegesis). Findings indicate the significance of the yellow cloth transformed: from traditional tabarruk (seeking blessings) to ta‘zhim (veneration)—a scholarly view aligned with tawhid. For the younger generation, it has transitioned into a symbol of cultural identity. This study concludes this phenomenon is not syncretism but a creative dialectic and cultural Islamization, shaping a localized "Banjar Islam."